ANALISA BERAT BEBAN HOISTING SYSTEM PADA OPERASI KERJA ULANG DAN PERBAIKAN SUMUR DI LAPANGAN ‘Y’ - Yehezkiel Kalapain; Leonardo Davinci Massolo (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2022)
Workover and well service (WOWS) is a set of operations related to the restoration of production well. On an Onshore Field “Y” there are several wells which currently ineffective in producing oil. Therefore, WOWS is needed to increase oil production. In performing WOWS there are several required systems to support operation such as the hoisting system. Calculating the total weight of the hoisting system requires estimation of vertical weight, horizontal weight, drilling line tension, and the required horsepower to overcome the total weight carried by the rig structure. These elements determine the rig types and draw work specifications. Furthermore, recognizing the hoisting system's ability on holding the WOWS string’s weight. Based on the calculation and analysis, the elements such as vertical weight, etc., are obtained. The calculated vertical weight is around 69,911 lbs., horizontal weight 619.43 lbs., drilling line tension 32,007 lbs., and the minimum required horsepower 297.88 Hp. This parameter sums up the total weight as 134,546 lbs. The results suggest that the rig tower is still safe and operable considering the maximum weight of the structure is double the total operating weight, around 264,554.4 lbs.